Effect of intravenous administration of zoledronic acid on jaw bone density in cases having skeletal metastasis: A prospective clinical study - Veena Jain; Ashu Seith; Smita Manchanda; Rajath Pillai; D N Sharma; Vijay Prakash Mathur (Wolters Kluwer Medknow Publications, 2019)
Aim: The objective is to evaluate the effect of intravenous (i.v.) administration of bisphosphonate (zoledronic acid) therapy on the jaw bone density and incidence of any other bony patholog. Settings and Design: Observational - prospective study. Materials and Methods: A total of 57 patients having a history of bony metastasis (excluding the jaw bone) were enrolled following the inclusion/exclusion criteria. Each patient received six doses of 4 mg i.v. bisphosphonate once a month. Multidetector computed tomography (MDCT) of jawbones for each patient was performed before the start of therapy (baseline) and subsequently at 6 and 12 months. Bone density was assessed at 24 predetermined sites (8 sites in maxilla and 16 sites in mandible) and any pathological change in either of the jaw bones was noted. Statistical Analysis Used: Shapiro-Wilk test ,Pearson's Chisquare test and repeated measures analysis of variance. Results: The result showed no statistically significant increase in mean bone density over a period of 1 year in maxilla and mandible. However, a significant increase in bone density was observed from 6 months to 1 year in mandibular anterior cancellous bone. The detailed observation of each MDCT scan showed no pathological change in either of the jaw bones during the study period. Conclusion: The administration (i.v.) of six doses of 4 mg bisphosphonate did not lead to a significant change in bone density over a period of 1 year.